Preoperative hyponatremia as a predictor of complicated acute appendicitis: a prospective observational study - Thobbi, Raksha R.; Agarwal, Garima; Bhadhoria, Aashima; Vardhan, Harsh; Patil, Vishwanath (International Journal of Research in Medical Sciences, 2026)
Background: Acute appendicitis is the most frequent surgical emergency and a leading cause of acute abdominal pain, carrying a lifetime risk of approximately 6%. Clinical presentation is often misleading and hyponatremia has been proposed as a biochemical marker for complicated acute appendicitis. This study evaluated the role of serum sodium as a marker of appendicitis severity. Methods: This hospital-based, observational prospective study was conducted in the department of general surgery, SMS Medical College, Jaipur, from August 2024 to September 2025, and enrolled 100 adult patients (>18 years) diagnosed with appendicitis. Patients were categorized into hyponatremic (serum sodium <135 mEq/l) and normonatremic groups. Data were collected on demographics, clinical presentation (Alvarado score), white blood cell count, surgical findings, and postoperative recovery. The primary objective was to evaluate serum sodium as a marker of appendicitis severity; secondary objectives were to assess its impact on surgical site infection rates and duration of hospital stay. Results: Hyponatremic patients (mean age 36.76±17.54 years) were significantly older and predominantly male compared with normonatremic patients. Gastrointestinal symptoms including nausea/vomiting (84% versus 32%) and anorexia (76% versus 48%), were more prevalent in the hyponatremic group, and 94% of hyponatremic patients required hospitalization for 3 days or longer, compared with 66% of normonatremic patients. Hyponatremia showed a strong association with complicated pathology, but its predictive value for surgical site infection was weak (16% versus 12%), and white blood cell counts lacked specificity for differentiating disease severity between groups. Conclusions: Serum sodium appears to be a reliable, objective surrogate marker for predicting complicated appendicitis, reflecting systemic inflammation and increased hospital resource utilization, and may aid early identification of high-risk patients who require urgent intervention, particularly when Alvarado scores are equivocal.